PSYCHOACTIVE SUBSTANCE ABUSE, WORK HOURS AND TASK STRUCTURE AS PREDICTORS OF STRESS SYMPTOMS AMONG INDUSTRIAL WORKERS - Ebeh, Richards E; Njoku, Ethelbert C (African Journal of Social and Behavioural Sciences, 2020)
This study examined psychoactive substance abuse, weekly work hours, task structure, gender and age as predictors of stress symptoms among industrial workers. Two hundred employees from the production and marketing departments of 7Up Bottling Company PLC at Oregun in Lagos State, Nigeria were drawn through convenience sampling technique. They were made up of 135 males and 65 females. Participants’ ages ranged from 18 – 43 years with a mean age of 27.69 years and a standard deviation of 5.35. The participants were measured using the Simple Screening Instrument for Substance Abuse (SSI-SA) and Psycho-Physiological Symptoms Checklist. The design used was the Cross-Sectional Survey Design while the Standard Multiple Regression on SPPS version 17 was used to analyze data collected. The results showed that psychoactive substance abuse, weekly work hours, task structure and gender significantly predicted stress symptoms among industrial workers. However, age did not significantly predict stress symptoms. The study recommends that Nigerian industries should streamline work hours to provide employees more time to relax. Also, psychoactive substance counselling sessions need to be undertaken regularly in Nigerian industries.